PENGARUH DIGITAL MARKETING, FoMo, DAN SOCIAL MEDIA INFLUENCER TERHADAP KEPUTUSAN PEMBELIAN PRODUK FASHION BRAND RUCAS (STUDI PADA GENERASI Z KOTA PURWOKERTO) - Restu Agung Pratama; Restu Frida Utami; Herni Justiana Astuti; Hermin Endratno (JURNAL ILMIAH EDUNOMIKA, 2026)
Competition in the Indonesian fashion industry is becoming increasingly fierce as trends evolve rapidly and consumer needs change. According to the Ministry of Industry, as quoted by Antara News, the fashion sector contributes significantly to the national economy, accounting for 6.96% of GDP in the second quarter of 2025 (Kurmala, 2025). Generation Z is the main driver of this growth due to their high awareness of appearance and the strong influence of social media trends on consumer behavior. One local brand that has gained significant attention from Generation Z is Rucas. This Jakarta-based streetwear brand, founded in 2019, offers exclusive products such as T-shirts and outerwear, with a limited purchase system of one product per release and no re-production, thus creating scarcity and increasing consumer interest. This study uses a quantitative method with a purposive sampling approach as part of a non-probability sampling method. The study population consists of Rucas product users living in Purwokerto City, with a total of 115 respondents. The results show that the variables of digital marketing, Fear of Missing Out (FOMO), and social media influencers influence purchasing decisions.